Notary’s Liability for Nominee Agreement on The Ownership of Land Rights by Foreigners in Bali - Rani, Ayu Sitha Radha (Universitas Medan Area, 2024)
The increasingly rapid development of the tourism sector in Bali has caused many people to want to live in Bali, including people from outside Indonesia who want to own land to use as a residence or business in the tourism sector in Bali. However, laws and regulations in Indonesia strictly prohibit this as stated in the UUPA. The high desire of foreign nationals to own land in Bali means that there are many ways to avoid existing regulations. The loopholes in the UUPA regulations have given rise to name borrowing agreements by foreign citizens so that their desire to own land in Bali can be realized. A normative juridical approach is used in this research as a research method. Legal materials were collected through inventory procedures and identification of statutory regulations using literature review data as the research techniques. The research results show that an authentic deed made by a notary gives rise to civil and criminal legal consequences, this is because the making of the agreement constitutes legal contravention which is clearly contrary to existing regulations, especially the UUPA, and based on the Civil Code, the agreement is null and void. As the maker of an authentic deed of a nominee agreement, a notary also has an unavoidable responsibility in the form of compensation if there are losses incurred as a result of the agreement. The notary can be criminalized for making false statements in a deed that is authentic/has legal force, in terms of responsibility. According to the notary's code of ethics, the notary may receive a reprimand, suspension and dismissal either honorably or dishonorably according to the results of the notary's code of ethics trial.